Use of Gadgets During Learning from Home Between Extrovert and Introvert Personality Types in Elementary School Students - Dyah Worwirastri Ekowati (Universitas Pendidikan Ganesha, 2022)
The Indonesian Government's policy during the covid-19 pandemic is Learning from home. This policy indirectly familiarizes students with various personality types to use gadget communication media. This study analyzes the use of gadgets while learning from home between extroverted and introverted personality types in elementary school. The research was conducted by case study and the type of research is descriptive. The research instruments are interviews, observation, and documentation. The subjects are 2 extroverted and 2 introverted elementary students as key informants. Data from interviews and observations were analysed qualitatively. The results showed that both extroverted and introverted students used gadgets with duration of more than 3 hours (high duration). Activities carried out according to the direction of each school are reading, doing, collecting assignments, and looking for supporting reference sources. Both personality types also use smartphones for social media, browsing favourite topics, and online games. Both have in common not being able to manage time well. The difference is that introverted students have not been able to manage time because they cannot make decisions for themselves. Meanwhile, extroverted students have not been able to manage time because there are more online games and social media. Both personality types require good mentoring.